Analyzing the Electoral Impact of Campaign Displays on Trees in Makassar’s 2024 Municipal Election - Rezkiawan Embas, Ade; Nurlinah, Nurlinah; Lukman Irwan, Andi (Journal of Neonatal Surgery, 2025)
This study examines the effectiveness of government efforts to protect trees in Makassar City from campaign prop violations during the 2024 election. Using a descriptive qualitative approach, data was collected through field observations, document analysis, and interviews with key stakeholders, including KPU, Bawaslu, and the Environmental Agency. Applying Public Policy Theory, the study analyzes policy formulation, implementation, and enforcement. Findings reveal that despite a clear legal framework, enforcement is hindered by limited resources, weak sanctions, and repeated violations. Trees, streetlight poles, and other prohibited areas continue to be used for campaign props, causing environmental damage. While authorities conduct regular clean-ups, new violations persist, highlighting gaps in deterrence and public compliance. This research underscores the need for stricter regulations, stronger enforcement, and public awareness campaigns to protect urban greenery. Future studies should explore long-term policy impacts, technology-driven enforcement, and community-based strategies to promote environmental responsibility during elections.